Surgical outcomes of stage IV non-small cell lung cancer: a single-center experience - Zhang, Chenxi (J Thorac Dis, 2019)
BACKGROUND: Increasing evidence has shown the effectiveness of surgery for stage IV non-small cell lung cancer (NSCLC). Present study aims to summarize the experience of our institution in dealing with advanced NSCLC in the context of multimodality therapy including lung surgery. METHODS: Patients underwent surgical resection for stage IV NSCLC diagnosed before or during surgery from January 2014 to June 2017 at Tangdu Hospital were included in this study. RESULTS: There were 88 stage IV NSCLC patients enrolled in this study. Among them, 35 patients with pleural metastases, 18 with brain oligometastases, 25 with extra-brain oligometastases and 10 with multiple metastatic sites or organs. For primary lung tumor, almost all (86/88) were resected with R0. For metastatic lesions, 53 patients received curative local treatment and 9 patients with partial treatment. There were 62 patients received adjuvant treatment, 10 patients received no adjuvant treatment and 16 patients with missing data of adjuvant treatment. The median overall survival of patients was 31.72 months. The estimated 3-year OS was 42.2%. Patients with pleural metastases and brain oligometastases got better outcomes than the ones with extra-brain oligometastases and multiple metastases (P<0.001). Patients with adjuvant epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) treatment had significantly better OS compared with those with adjuvant chemotherapy treatment (P=0.015). Besides, age <60 and cT1-2 were also associated with better survival. CONCLUSIONS: Surgery may be a considerable choice for stage IV NSCLC in the context of multimodality therapy.